THE EFFECTS OF GIBBERELIC ACID ON CLUSTER GRAPE MORPHOLOGY CHARACTERISTICS CULTIVAR A DONA AND MARTE - TECCHIO, Marco Antonio; MOURA, Mara Fernandes; HERNANDES, Jose Luiz; PAIOLI-PIRES, Erasmo José; TERRA, Maurilo Monteiro; LEONEL, Sarita (Scientia Agraria, 2009)
The research was carried out in the grapes cultivars A Dona and Marte at Jundiaí-SP, with a purpose to evaluate the effect of the gibberelic acid (GA3) on the morphology and chemical characteristics of the clusters and berries grape. For A Dona cultivar, the treatments consisted of four concentrations of GA3: 0, 10, 20 and 30 mg dm-3 applied by dipping of clusters. The GA3 was applied 20 days after the bloom. ‘A Dona’ was grafted on ‘Riparia of Traviu’ and ‘IAC 766’ rootstocks. For Marte cultivar, the treatments consisted of five concentrations of GA3: 0, 15, 30, 45 and 60 mg dm-3. The characteristics evaluated were fresh weight of clusters, berries and rachis; length and diameter of clusters and berries, berries number and soluble solid contents. It was concluded that, to cultivate A Dona there was no interaction among the concentrations of GA3 and the rootstocks, but however, significant improvement in the characteristics of clusters with the rootstock 'IAC 766'. In relation the GA3 concentrations analyzed through regression it was verified that the 20 mg dm-3 of GA3 enhanced about 75, 63 and 9% respectively, the fresh weight of clusters, berries and rachis, and about 8 and 15% on length and diameter of clusters and 20 and 10% on berries length and diameter and 16% on the berries number. For A Dona cultivar the GA3 at 20 mg dm-3 was the best concentration. For Marte cultivar, it was observed linear increase for all the characteristics evaluated, therefore, it was recommended the utilization of the 60 mg dm-3 of GA3.